Development of 24-pulse Thyristor Converter with Optimal Power - LIANG Wenkun; LAI Yubin; FANG Changshi (Kongzhi Yu Xinxi Jishu)
In view of these problems on the harmonic current and the reactive power loss in thyristor converter, a new main circuit scheme for 24-pulse thyristor converter with saving of power is presented in this paper. The configuration and operating principle of the converter are introduced. Commutating processes on both the conventional mode and the optimal power mode are analyzed. The mathematics model and the minimum inverting angle of safety commutation on the inverting region are derived too. Moreover, the function and operating process of firing angle regulator are discussed. Finally, the tested load voltage waveforms and experimental data are given. Experimental results agreement with the theoretical analysis.